Motor Show (Module II, 2013)
England. London, Earls Court. General view of interior of motor show. Clip includes footage of: New Austin Mini Minor turning on platform; Austin Mini on stand cut in half to show engine and Austin Mini without engine cover. Includes shots of Ford Popular, Ford Anglia, Austin Countryman, Citroen, Dauphine, Fiat, Corvair, Falcan, Daimler and Bentley.